The use of sulphate-reducing bacteria in bioremediation of ex-coal mining soil - ENNY WIDYATI (Biodiversitas Journal of Biological Diversity, 2007)
The most serious impact after exploiting coal by opened peat mining is acid mine drainage phenomenon. This is an oxidation of sulphide minerals by releasing sulphate that generate the environment acidity. This study was aimed to observe the ability of sulphate reducing bacteria (SRB) isolated of sludge paper mills in decreasing the ex-coal mining sulphate content. Before inoculating onto the soil, SRB was incubated in the sterilized organic matter for 4 days. Organic matter inhabited SRB mix with ex-coal mining soil (1:3 v/v). As a control was a series ex-coal mining mixed with non inoculated organic matter (1:3 v/v). The experiment is carried out in randomized complete design in 3 replications, each consist of 5 buckets. All buckets were maintained in saturated water content. Every 5 days for 20 days the sulphate content, pH and Eh were assessed to observe the bioremediation progress. The result shown that SRB was able to reduce 84.25% excoal mining sulphate content in 20 days. In consequence, the soil pH was increased from 4.15 to 6.66 during the process. It is recommended that SRB is prospective to be further developed as a sulphate bioremediation agents on ex-coal mining soil.Â© 2007 Jurusan Biologi FMIPA UNS SurakartaKey words: bioremediation, ex-coal mining, sulphate reducing bacteria